TERHADAP KEPATUHAN PENGUNGKAPAN PSAK 46 PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2016 - Pernando Simamora M; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to examine the influence of corporate governance factors to PSAK 46 in annual reports of manufacturing companies that listed on the Indonesia Stock Exchange in the year 2014-2016. Factors of corporate governance used in this study is independency board of commisioners, foreign member in board of commisioners, size board of commisioners, managerial ownership and audit quality.The population of this study are all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the year 2014-2016. Total sample are 134 annual reports of manufacturing companies as determined by purposive sampling method. This research analyzes PSAK 46 disclosure in annual reports by the method of content analysis. Data analysis was performed with the classical assumption, dummy test and hypothesis testing of regression method.The results of this study indicate that independency board of commissioners, foreign member in board of commisioners, size board of commisioners and managerial ownership did not have significant influence to the PSAK 46 disclosure. Audit quality have significant influence to PSAK disclosure.